Effect of 8 Weeks of Combined Plyometric Training on Increasing Lower and Upper Body Muscle Power in Student Volleyball Athletes - Muhammad, Muhammad; Kusnanik, Nining Widyah; Pramono, Bayu Agung (Physical Education Theory and Methodology, 2023)
The study purpose was to identify the effects of a combination of plyometric exercises in the increasing leg and arm power abilities of volleyball athletes. Materials and methods. Forty students were involved in this study. They were students who were active in practicing volleyball, and then they were divided into four groups of 10 students each, namely (1) Squat thrust jumps and clap push-ups, (2) Squat thrust jumps and lateral push-ups, (3) Rope jumps and clap push-ups; and (4) Rope jumps and lateral push-ups. Then they practiced plyometrics three times a week for eight weeks. Statistical analysis used the t-test and the N-Gain Score using the Statistical Package for Social Science (SPSS) version 26 program. Results. The results of the combination of plyometric exercises stated that it had an effect on the muscle power of both the legs and arms (p<0.05); then, the results showed the combination of squat thrust and lateral push-up exercises was effective in increasing the ability of leg muscle power by 84.43% while the variety of squat thrust jump exercises and clap push-ups provide effectiveness in increasing arm muscle power by 25.23%. Conclusions. The variety of these two types of plyometric exercises was successful in helping volleyball athletes improve their vertical jump abilities. Still, from the results of this study, it was not very effective in increasing the capacity of arm muscle power.